Cost-Effectiveness Analysis of Insulin Detemir Compared to Neutral Protamine Hagedorn (NPH) in Patients with Type 1 and Type 2 Diabetes Mellitus in Spain. Issue 4 (December 2015) - Morales, Cristóbal; Luis, Daniel; Arellano, Antonio; Ferrario, Maria; Lizán, Luis
Abstract Introduction An Excel® (Microsoft Corporation) model was adapted to estimate the short-term (1-year) cost effectiveness of insulin detemir (IDet) versus neutral protamine Hagedorn (NPH) insulin in patients initiating insulin treatment with type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM) in Spain. Methods Clinical benefits included the non-severe hypoglycemia rate for T1DM and T2DM, and weight change for T2DM. Three scenarios were included with different hypoglycemia rates estimated on the basis of clinical trials and observational studies. Costs, estimated from perspective of the Spanish Public Healthcare System (Euros 2014), included insulin treatment and non-severe hypoglycemia management costs. Non-severe hypoglycemia, defined as a self-managed event, implied the use of extra glucose testing strips and a general practitioner visit during the week following the event for 25% of patients. An average disutility value was associated to non-severe hypoglycemia events and, for T2DM, to one body mass index unit gain to calculate quality-adjusted life years (QALYs). Results For the three scenarios a range of 0.025–0.076 QALYs for T1DM and 0.014–0.051 QALYs for T2DM were gained for IDet versus NPH due to non-severe hypoglycemia and weight gain avoidance, in return of an incremental cost of €145–192 for T1DM and €128–206 for T2DM. This resulted in the IDet versus NPH incremental cost-effectiveness ratio (ICER) ranging between €1910/QALY and €7682/QALY for T1DM and €2522/QALY and €15, 009/QALY for T2DM. Conclusion IDet was a cost-effective alternative to NPH insulin in the first year of treatment of patients with T1DM and patients with T2DM in Spain, with ICERs under the threshold value commonly accepted in Spain (€30, 000/QALY). Funding Novo Nordisk.